Pengembangan Proyek Sistem Informasi Penjualan Laptop Berbasis Web pada Bless Computer - Manurung, Desky Olivia; Venansia, Apriliana; Fatmawati, Fatmawati (BINA INSANI ICT JOURNAL, 2024)
With the use of information technology today, business actors in managing their business utilize technology with marketing media that are currently many such as online stores that can market their products widely so that sales increase. Bless Computer is one of the stores that sells laptops, computers, and various computer accessories. In its business practice, the store has not utilized online media in all aspects of the store. The current store sales system is desktop-based and the stock of goods in the store is still manual so an information system is needed for online and offline business processes. From the problems studied, the author concludes to create a web-based sales system that is applied with PHP programming language and MySQL database. The design of this system is also supported by a software development method known as the Software Development Life Cycle (SDLC) waterfall model to facilitate the planning process, stages of making, and testing of the system created. The results of the research obtained are the Bless Computer store laptop sales website which is made as attractive as possible and contains information about the Bless Computer store so that it is easily known by many people to purchase laptops and accessories more easily to increase sales.